Distribution of antibiotic resistance genes in Staphylococcus epidermidis clinical isolates - Farqad Reyad Faihan; Ali Hazem Abdulkareem (Advancements in Life Sciences, 2026)
Background: Staphylococcus epidermidis is an opportunistic pathogen associated with hospital-acquired infections and increasing antibiotic resistance. This study aimed to determine the prevalence of Staphylococcus epidermidis in selected clinical samples and to investigate the distribution of antibiotic resistance genes in isolates.Methods: A total of 164 clinical samples were collected from Al-Ramadi Teaching Hospital and Al-Ramadi Maternity & Children Teaching Hospital in Al-Anbar, Iraq, during the period from August 2021 to December 2021. Samples were obtained from wounds, kidney stones, eyes, and skin, representing common clinical sources of Staphylococcus infections. Identification of isolates was performed using standard biochemical tests and the VITEK 2 Compact system with GP-ID cards. Polymerase chain reaction (PCR) was used to detect selected antibiotic resistance genes (mecA, ermA, ermC, tetK, and aacA-D) associated with resistance to commonly used antibiotics.Results: Out of 164 clinical samples, 24 (14.63%) were positive for Staphylococcus epidermidis, while 140 (85.37%) were negative for Staphylococcus epidermidis. PCR analysis revealed that the mecA gene was detected in 24/24 isolates (100%), the ermC gene in 24/24 isolates (100%), the ermA gene in 3/24 isolates (12.5%), the tetK gene in 24/24 isolates (100%), and the aacA-D gene in 10/24 isolates (41.7%).Conclusion: The findings indicate a high prevalence of antibiotic resistance genes among Staphylococcus epidermidis isolates in the studied hospitals. However, the study is limited by the relatively small number of S. epidermidis isolates and its restriction to specific healthcare facilities in Al-Anbar, Iraq. Further studies with larger and more diverse sample populations are recommended to better understand the epidemiology of antibiotic resistance in S. epidermidis.Keywords: Staphylococcus epidermidis, Antibiotic resistance genes, Antibiotic resistance